SCHEDULING ANALYSIS OF PLAN, REALISATION, AND ESTIMATION BY USING PRECEDENCE DIAGRAM METHOD (PDM) (CASE STUDY : CONSTRUCTION DEVELOPMENT PROJECT MULTI-PURPOSE SPORTS HALL PHASE IV IN KATINGAN REGENCY) - Putri, Dhika Fitrianita; Widiastuti, Endah; Afrila, Humaira; Hidayat, Gawit (CERUCUK, 2025)
In its implementation, starting from planning, scheduling implementation, to supervision and implementation of controls properly, construction projects have a complicated and dependent series at each stage. In the process of Construction of Phase IV Multipurpose Sports Building located in Katingan Regency, there were delays due to several obstacles. This is related to time management, thus affecting the delay in project completion. This study aims to analyse the difference in the period of delay that occurs based on the scheduling plan, realisation, and estimation with the help of Microsoft Project 2021, as well as identifying the critical and non-critical path of work on the three schedules. In this study, the quantitative analysis method, where data collection was carried out by interviewing and distributing questionnaires to several respondents from Supervisory Consultants and distribution of questionnaires to several respondents from the Supervisory Consultant and Implementing Contractor with a total of 6 respondents.Based on the results of PDM analysis with the help of Microsoft Project 2021, a comparison of the total duration of work based on plan, realisation and estimation scheduling was obtained, namely in the plan scheduling for 272 days, realisation scheduling for 249 days, and estimation scheduling for 267 days.Based on the three schedules, the work with the most critical status is obtained in Preparatory Work, Concrete Structures, Doors and Windows, Electrical and Electrical, and Procurement of Equipment Etc. And from the results of the questionnaire recapitulation, it is concluded that the influencing factors in the construction process of this project are unstable weather, material supply mobilisation process, and lack of manpower. Keywords : Critical and Non-Critical Path, Microsoft Project 2021, Rescheduling, Precedence Diagram Method (PDM)